Electro-catalyst with low noble metal loading capacity as well as preparation method and application of electro-catalyst
By using a low-precious metal loading electrocatalyst, which includes Co3O4 nanosheets and precious metal single atoms, solves the problems of slow kinetics of glycerol oxidation reaction and low selectivity of C3 products, achieving high activity and high selectivity catalysis, reducing costs.
Patent Information
- Application Number
- CN202411850861.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-16
- Publication Date
- 2025-04-08
- Estimated Expiration
- 2044-12-16
AI Technical Summary
In neutral media, the kinetics of the glycerol oxidation reaction are slow and the high added value C3 products are low selectivity, making it difficult for the prior art to achieve high activity and high selectivity catalysis under near neutral conditions.
Using a low noble metal loading electrocatalyst, the catalyst including Co3O4 nanosheets distributed arrays on the self-supporting support and precious metal single atoms supported on the Co3O4 nanosheets, a catalyst with high activity and high selectivity is prepared by a specific preparation method.
Under near neutral conditions, a glycerol oxidation reaction with high activity and high C3 product selectivity was achieved. The high selectivity and stability of the catalyst significantly improved the product selectivity of glyceraldehyde, reduced the use of precious metals and reduced the cost.
Smart Images

Figure CN119776902A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of inorganic nanomaterials, and specifically relates to a low-noble metal-loaded electrocatalyst for glycerol small molecule value-added electro-oxidation in a neutral medium and a preparation method thereof. Background Art
[0002] Glycerol is a low value-added byproduct in the industrial production of biodiesel (accounting for about 10wt.% of the total product). At the same time, glycerol is listed as one of the top ten biomass-derived platform molecules by the U.S. Department of Energy, which is of great significance for the conversion of glycerol into high value-added chemicals. Compared with traditional glycerol oxidation technology, driven by green electricity such as solar energy and wind energy, the electrocatalytic glycerol oxidation reaction (GOR) produces high value-added chemicals, which has the advantages of being environmentally friendly, sustainable and efficient. GOR can produce a variety of high value-added products such as glyceraldehyde, dihydroxyacetone, glyceric acid, glycolic acid, formic acid, etc. Therefore, it is of great significance to develop electrocatalysts for glycerol oxidation reaction with high activity and high product selectivity.
[0003] Among the many oxidation products, high value-added glyceraldehyde (a C3, aldehyde compound) has great application prospects, and the highly selective preparation of C3 aldehyde compounds is of great research value. However, the commonly used alkaline medium (such as 1MKOH) seriously hinders the synthesis of aldehyde products, because aldehydes will be converted into geminal diols after hydration in alkaline media, and further oxidized to obtain carboxylic acid products. On the other hand, aldehydes may undergo side reactions such as aldol condensation and dimerization in alkaline media and cannot exist stably. In addition, strong bases can also corrode devices. Therefore, in order to circumvent these problems, a near-neutral medium is selected as the reaction electrolyte. However, under neutral conditions, the lack of strong nucleophilic reagents OH - , insufficient active centers lead to slow reaction kinetics of glycerol in neutral medium and low selectivity of high value-added C3 products.
[0004] Therefore, it is of great significance to develop GOR catalysts that can achieve high activity and high product selectivity in near-neutral media. Summary of the invention
[0005] In view of the above technical problems, the present invention provides a GOR electrocatalyst with low noble metal loading that can achieve high activity and high C3 product selectivity in a near-neutral medium, as well as a preparation method and application thereof.
[0006] In a first aspect, the present invention provides a low-noble metal loading electrocatalyst, the low-noble metal loading electrocatalyst comprising: a self-supporting carrier, Co3O4 nanosheets supported on the self-supporting carrier and distributed in an array, and noble metal single atoms supported on the Co3O4 nanosheets; Wherein, the noble metal single atom includes at least one of a Pt single atom, a Pd single atom and a Ru single atom.
[0007] Preferably, the self-supporting carrier is at least one of nickel foam, copper foam, and cobalt foam, preferably nickel foam; The diameter of the Co3O4 nanosheet is 400-800nm, preferably 500-800nm, more preferably 500nm, and the thickness is 5-30nm.
[0008] Preferably, the loading amount of Co3O4 nanosheets on the surface of the self-supporting carrier is 4 to 20 mg / cm 2 The mass ratio of the noble metal single atom to the Co3O4 nanosheet is 1:(50-200).
[0009] In a second aspect, the present invention provides a method for preparing the above-mentioned low noble metal loading electrocatalyst, the preparation method comprising the following steps: (1) mixing a solution containing a cobalt source, a noble metal source and a precipitant to obtain a precursor solution; (2) placing the self-supporting carrier into the above-mentioned precursor solution to allow the cobalt source and the noble metal source to undergo nucleation growth, and washing and drying after the growth is completed to obtain a noble metal-cobalt hydroxide nanosheet array supported on the self-supporting carrier; (3) heat-treating the noble metal-cobalt hydroxide nanosheet array supported on the self-supporting carrier under a protective atmosphere to obtain the low noble metal loading electrocatalyst.
[0010] Preferably, in step (1), the cobalt source is at least one of cobalt nitrate hexahydrate, cobalt sulfate heptahydrate, and cobalt chloride hexahydrate, preferably cobalt nitrate hexahydrate; The noble metal source includes at least one of a platinum source, a palladium source, and a ruthenium source; wherein: the platinum source is at least one of chloroplatinic acid hexahydrate, potassium chloroplatinate, ammonium hexachloroplatinate, and platinum acetylacetonate; the palladium source is at least one of palladium dichloride, palladium nitrate dihydrate, and palladium acetylacetonate; the ruthenium source is at least one of ruthenium trichloride hydrate, ruthenium dioxide, and ruthenium acetylacetonate, preferably ruthenium trichloride hydrate; The precipitant is at least one of urea, hexamethylenetetramine and ammonium fluoride, preferably hexamethylenetetramine.
[0011] Preferably, in step (1), the mass ratio of the cobalt source to the noble metal source is 50-290:1; and the molar ratio of the cobalt source to the precipitant is 1:1-5.
[0012] Preferably, in step (2), 0.1 to 4 cm 2 Self-supporting carrier.
[0013] Preferably, in step (2), the nucleation growth process is: keeping warm at 80-150° C. for 4-16 hours.
[0014] Preferably, in step (3), the protective atmosphere is air, the heat treatment temperature is 300 to 550° C., preferably 350 to 550° C., and the heat treatment time is 1 to 4 hours.
[0015] In a third aspect, the present invention provides an application of the above-mentioned low noble metal loading electrocatalyst in the electrocatalytic glycerol value-added oxidation under near-neutral conditions.
[0016] Beneficial Effects (1) The Ru-Co3O4 / NF catalyst provided by the present invention continuously generates CoOOH active species in situ in GOR, which improves the GOR reaction kinetics while regulating the adsorption mode of glycerol, achieving a primary alcohol oxidation pathway of glycerol as the main pathway, and obtaining a C3 product selectivity of >90%; (2) The present invention successfully prepares a cobalt tetroxide nanoarray loaded with a single noble metal atom by a "hydrothermal method", which increases the specific surface area while exposing active sites, achieving rapid material transport and thus obtaining a high current density; (3) The preparation method of the present invention prepares a high-utilization low-precious metal content catalyst by reducing the precious metal content (Ru dosage can be 0.5-2wt.%) and improving the dispersion of the precious metal (existing in the form of single atoms) to reduce costs. The preparation conditions are mild and simple, and it has high economic benefits and practical value. BRIEF DESCRIPTION OF THE DRAWINGS
[0017] Figure 1 The SEM images of Co3O4 / NF prepared in Comparative Example 1 (a), 5-Ru-Co3O4 / NF prepared in Example 1 (b), and RuO prepared in Comparative Example 2 (c) are shown in Figure 1. x / NF prepared in Comparative Example 3 (c) and (d) NF prepared in Comparative Example 3; Figure 2 The XRD pattern of Co3O4 / NF prepared in Comparative Example 1 (a) and the XRD pattern of 5-Ru-Co3O4 / NF prepared in Example 1 (b); Figure 3 TEM image (a) and selected area TEM image (b) of Co3O4 / NF prepared in comparative example 1, TEM image (c) and selected area TEM image (d) of 5-Ru-Co3O4 / NF prepared in example 1; Figure 4 The Raman graph of Co3O4 / NF prepared in Comparative Example 1 (a) and the Raman graph of 5-Ru-Co3O4 / NF prepared in Example 1 (b); Figure 5 The LSV (Linear Sweep Voltammetry) curves of 5-Ru-Co3O4 / NF prepared in Example 1 with and without glycerol added (a) and the Co3O4 / NF prepared in Comparative Example 1 and the RuO x LSV curves of Ru / Co3O4-NF prepared in Example 4, Comparative Example 4 and 5-Ru-Co3O4 / NF prepared in Example 1 with glycerol added (b), where the curves in (a) are respectively with glycerol added and without glycerol added from top to bottom, and the curves in (b) are respectively with Example 1, Comparative Example 4, Comparative Example 1 and Comparative Example 2 from top to bottom; Figure 6 The Co3O4 / NF prepared in Comparative Example 1, the 5-Ru-Co3O4 / NF prepared in Example 1, and the RuO prepared in Comparative Example 2 x / NF prepared in comparative example 1, 5-Ru-Co3O4 / NF prepared in example 1, and Nyquist curve of EIS (electrochemical impedance spectroscopy) of Co3O4 / NF prepared in comparative example 1 and 5-Ru-Co3O4 / NF prepared in example 1 (c); Figure 7 The product selectivity diagram (a) and the C3 product selectivity and C3 product yield diagram (b) of Co3O4 / NF prepared in Comparative Example 1, the columns in (a) are glyceric acid, glyceraldehyde, and dihydroxyacetone from top to bottom, respectively, and the left y-axis in (b) corresponds to the C3 product selectivity and the right y-axis corresponds to the C3 product yield; Figure 8 The product selectivity diagram (a) and the C3 product selectivity and C3 product yield diagram (b) of 5-Ru-Co3O4 / NF prepared in Example 1, the columns in (a) are glyceric acid, glyceraldehyde, and dihydroxyacetone from top to bottom, respectively, and the left y-axis in (b) corresponds to the C3 product selectivity and the right y-axis corresponds to the C3 product yield; Fig. 9 CP (chronovoltage) curve of 5-Ru-Co3O4 / NF prepared in Example 1; Fig.10 The Co3O4 / NF prepared in Comparative Example 1 and the RuO prepared in Comparative Example 2 x / NF, 5-Ru-Co3O4 / NF prepared in Example 1, 7-Ru-Co3O4 / NF prepared in Example 2, 9-Ru-Co3O4 / NF prepared in Example 3 and 3-Ru-Co3O4 / NF prepared in Example 4 with the addition of glycerol; wherein the curves from top to bottom are respectively Example 1, Example 2, Example 4, Comparative Example 1, Example 3 and Comparative Example 2. DETAILED DESCRIPTION
[0018] The present invention is further described below by the following embodiments. It should be understood that the following embodiments are only used to illustrate the present invention, but not to limit the present invention.
[0019] First, the present invention provides a low-noble metal loading electrocatalyst, wherein the low-noble metal loading electrocatalyst may include: a self-supporting carrier, Co3O4 nanosheets supported on the self-supporting carrier and distributed in an array, and noble metal single atoms supported on the Co3O4 nanosheets; preferably, the noble metal single atoms may include at least one of Pt single atoms, Pd single atoms, and Ru single atoms.
[0020] In some embodiments, the self-supporting carrier may be at least one of nickel foam (NF), copper foam, and cobalt foam, preferably nickel foam.
[0021] In some embodiments, the diameter of the Co3O4 nanosheets may be 400-800 nm, preferably 500-800 nm, more preferably 500 nm, and the thickness may be 5-30 nm. The present invention adopts a relatively larger diameter and thinner nanosheet morphology with more active centers, more abundant edge active sites and rapid interface charge transfer capability, which is conducive to improving the overall catalytic performance.
[0022] In some embodiments, the loading amount of Co3O4 nanosheets on the surface of the self-supporting carrier can be 4 to 20 mg / cm 2 .
[0023] In some embodiments, the mass ratio of the noble metal single atom to the Co3O4 nanosheet can be 1:(50-200). In this way, the synergistic effect of Co3O4 and noble metal single atoms can be fully utilized. When the noble metal loading is too high, the noble metal is easy to agglomerate into nanoparticles or clusters, which will lead to excessive adsorption of glycerol and is not conducive to the GOR reaction. By reducing the noble metal content to increase the dispersion of the noble metal (existing in the form of single atoms) to prepare a high-utilization low-noble metal content catalyst, costs can be reduced, and it has high economic benefits and practical value. Moreover, this distribution method causes the active sites to be fully exposed, thereby promoting rapid and efficient reactions.
[0024] In the low noble metal loading electrocatalyst provided by the present invention, due to the difference in electronegativity between Co and the noble metal, Co with low electronegativity transfers electrons to the noble metal, which is conducive to the adsorption of OH by Co with more positive charge. -Thus, hydroxylation to hydroxy oxide accelerates the oxidation reaction of glycerol. In addition, noble metals have the best adsorption capacity for oxygen-containing intermediates, effectively adjusting the adsorption configuration of glycerol, thereby achieving the effect of highly selective production of C3 products.
[0025] The following is an exemplary description of the preparation method of the low noble metal loading electrocatalyst provided by the present invention. The preparation method may include the following steps: (1) mixing a solution containing a cobalt source, a noble metal source and a precipitant to obtain a precursor solution; (2) placing the self-supporting carrier into the above-mentioned precursor solution to allow the cobalt source and the noble metal source to undergo nucleation growth, and washing and drying after the growth is completed to obtain a noble metal-cobalt hydroxide nanosheet array supported on the self-supporting carrier; (3) heat-treating the noble metal-cobalt hydroxide nanosheet array supported on the self-supporting carrier under a protective atmosphere to obtain the low noble metal loading electrocatalyst.
[0026] In some embodiments, in step (1), the cobalt source may be at least one of cobalt nitrate hexahydrate, cobalt sulfate heptahydrate, and cobalt chloride hexahydrate, preferably cobalt nitrate hexahydrate.
[0027] In some embodiments, in step (1), the precious metal source may include at least one of a platinum source, a palladium source, and a ruthenium source; wherein: the platinum source may be at least one of chloroplatinic acid hexahydrate, potassium chloroplatinate, ammonium hexachloroplatinate, and platinum acetylacetonate; the palladium source may be at least one of palladium dichloride, palladium nitrate dihydrate, and palladium acetylacetonate; the ruthenium source may be at least one of ruthenium trichloride hydrate, ruthenium dioxide, and ruthenium acetylacetonate, preferably ruthenium trichloride hydrate.
[0028] In some embodiments, in step (1), the precipitant may be at least one of urea, hexamethylenetetramine, and ammonium fluoride, preferably hexamethylenetetramine. The precipitant may play the role of a nucleating agent, and the cobalt source may react with the precipitant to generate an alkaline environment and increase the rate of nucleation growth.
[0029] In some embodiments, in step (1), the mass ratio of the cobalt source to the noble metal source may be 50-290:1, preferably 50-200:1; the molar ratio of the cobalt source to the precipitant may be 1:1-5. By controlling the mass ratio of the cobalt source to the noble metal source within the above range, it is easier to control the distribution of the noble metal in the form of single atoms during the subsequent heat treatment process; controlling the molar ratio of the cobalt source to the precipitant within the above range can obtain a more uniformly distributed nanosheet array.
[0030] In some embodiments, in step (1), 5 to 30 mL of solvent may be used for every 1 mmol of the cobalt source; preferably, the solvent may be at least one of methanol, ethanol, and deionized water, preferably deionized water.
[0031] In some embodiments, in step (1), the solution can be uniformly mixed by ultrasound and stirring; preferably, the mixed solution is ultrasound-treated for 3 to 10 minutes and stirred at room temperature for 0.1 to 1 hour to mix uniformly. As an example, the raw material is prepared according to the molar ratio of cobalt nitrate to hexamethylenetetramine of 1: (1 to 5) and the mass ratio of cobalt source to ruthenium source of 50-200: 1, 5 to 30 mL of deionized water is added to every 1 mmol of cobalt nitrate, ultrasound-treated for 3 to 10 minutes, and stirred at room temperature for 0.1 to 1 hour to mix uniformly to obtain a precursor solution.
[0032] In the preparation method provided by the present invention, the solution of the cobalt source, the noble metal source and the precipitant is directly mixed to obtain a precursor solution. Compared with the traditional synthesis method, the preparation process is simple, efficient and convenient. By directly mixing the solution of the cobalt source, the noble metal source and the precipitant, the noble metal single atom can be doped into the lattice of the Co-based oxide, and the different sites of the noble metal single atom incorporation can be selectively controlled to improve the atomic utilization of the single atom, thereby effectively reducing the cost. In addition, directly mixing the raw materials can avoid the cumbersome synthesis process on the one hand, and on the other hand, it can avoid the agglomeration of the noble metal source in the subsequent synthesis process, generating unnecessary nanoparticles or clusters, thereby maximizing the synthesis of the noble metal single atom.
[0033] In some embodiments, in step (2), 0.1 to 4 cm 2 Self-supporting carrier.
[0034] In some embodiments, in step (2), the nucleation growth process can be: 80-150°C for 4-16 hours. In this way, the cobalt source can be uniformly nucleated to form a nanosheet array and the uniform doping of the noble metal source can be promoted. If the hydrothermal temperature is too low and the time is too short, it is not conducive to the formation of the nanosheet array; if the temperature is too high and the time is too long, it is not conducive to the uniform doping of low-load noble metal single atoms.
[0035] In some embodiments, in step (2), the drying temperature may be 20 to 80°C.
[0036] In some embodiments, in step (3), the protective atmosphere may be air, the heat treatment temperature may be 300 to 550° C., preferably 350 to 550° C., and the heat treatment time may be 1 to 4 hours. If the heat treatment temperature is too low, the nitrogen source contained in the precursor cannot be completely removed; if the heat treatment temperature is too high, the morphology is easily changed.
[0037] The catalyst provided by the present invention can reach 10 mA cm at a near-neutral condition (e.g. pH = 8) with only 1.16 V vs. RHE. -2 The current density can reach 200mAcm at only 1.84V vs.RHE. -2 Moreover, due to the difference in electronegativity between Co and noble metals, Co with low electronegativity transfers electrons to the noble metal, which is conducive to the adsorption of OH by Co with more positive charge. - The hydroxylation generates oxyhydroxide active species, thereby accelerating the oxidation reaction kinetics of glycerol. Therefore, the GOR activity of the catalyst is enhanced. In addition, the noble metal has the best adsorption capacity for oxygen-containing intermediates, effectively adjusting the adsorption configuration of glycerol, thereby achieving a C3 product selectivity of >90% in a wide potential range.
[0038] The nanocatalyst provided by the present invention presents an orderly array of nanosheets as a whole, can have high GOR activity and high C3 product selectivity in a near-neutral medium, and can stably operate for more than 100 hours during the IT test. In addition, the preparation method of the present invention has mild conditions and is easy to operate. The present invention solves the problem of the lack of strong nucleophilic reagent OH under near-neutral conditions. - , the slow reaction kinetics of glycerol in neutral medium due to insufficient active centers, and the low selectivity of high value-added C3 products.
[0039] The nanocatalyst of the present invention has excellent GOR activity, high C3 product selectivity and good GOR electrocatalytic stability in a near-neutral environment, and can be applied to electrocatalytic glycerol value-added oxidation under near-neutral conditions.
[0040] The following further examples are given to illustrate the present invention in detail. It should also be understood that the following examples are only used to further illustrate the present invention and cannot be construed as limiting the scope of protection of the present invention. Some non-essential improvements and adjustments made by those skilled in the art based on the above content of the present invention all belong to the scope of protection of the present invention. The specific process parameters of the following examples are also only examples within a suitable range, that is, those skilled in the art can make selections within a suitable range through the description of this article, and are not limited to the specific values exemplified below. If not specifically stated, the technical means used in the embodiments are conventional means well known to those skilled in the art.
[0041] Unless otherwise specified: The electrocatalytic activity was tested by the three-electrode method using a Shanghai Chenhua CHI 760E electrochemical workstation; the reference electrode was an Ag / AgCl electrode, the counter electrode was a carbon rod, and the scanning voltage range was -0.1 to 1.4 V (vs. Ag / AgCl); the electrocatalytic activity test was carried out by electrocatalytic glycerol oxidation in a 0.1 M KHCO3 plus glycerol aqueous solution in a near-neutral environment.
[0042] Example 1
[0043] The preparation method of the low noble metal loading electrocatalyst provided in this embodiment comprises the following steps: At room temperature, 0.87 g (3 mmol) of cobalt nitrate hexahydrate, 0.005 g of RuCl3·H2O and 6 mmol of hexamethylenetetramine were added to 80 mL of deionized water, ultrasonicated for 5 minutes and stirred at room temperature for 1 hour to obtain a uniform mixed solution; Place a 10cm 2 The nickel foam (NF) was used as a self-supporting body, which was kept at 120°C in an oven for 12 h. The self-supporting body was then taken out, washed with water, and vacuum dried to obtain a nano-array of Ru-Co(OH) x / NF precursor; Take an area of 2cm 2 Ru-Co(OH) x The / NF precursor was placed in a crucible, calcined at 400°C for 3 h in a tube furnace, and taken out after cooling to room temperature to obtain a Ru-Co3O4 / NF nanocatalyst material with a nano-array (labeled as 5-Ru-Co3O4 / NF).
[0044] Example 2
[0045] The preparation method of the low noble metal loading electrocatalyst provided in this embodiment refers to that in Example 1, the main difference is that 0.007 g RuCl3·H2O is added to the raw material, and the prepared Ru-Co3O4 / NF nanocatalyst material with nano-array is marked as 7-Ru-Co3O4 / NF.
[0046] Example 3
[0047] The preparation method of the low noble metal loading electrocatalyst provided in this embodiment refers to that in Example 1, the main difference is that 0.009 g RuCl3·H2O is added to the raw material, and the prepared Ru-Co3O4 / NF nanocatalyst material with nano-array is marked as 9-Ru-Co3O4 / NF).
[0048] Example 4
[0049] The preparation method of the low noble metal loading electrocatalyst provided in this embodiment refers to that in Example 1, the main difference is that 0.003 g RuCl3·H2O is added to the raw material, and the prepared Ru-Co3O4 / NF nanocatalyst material with nano-array is marked as 3-Ru-Co3O4 / NF).
[0050] Comparative Example 1
[0051] The preparation method of the catalyst material provided in this comparative example refers to that in Example 1, the main difference is that no RuCl3·H2O is added to the raw material, and finally a Co3O4 / NF nanocatalyst material (labeled as Co3O4 / NF) is obtained.
[0052] Comparative Example 2
[0053] The preparation method of the catalyst material provided in this comparative example is similar to that in Example 1, the main difference is that no cobalt nitrate is added to the raw material, and finally RuO x / NF nanocatalyst materials (labeled as RuO x / NF).
[0054] Comparative Example 3
[0055] The preparation method of the catalyst material provided in this comparative example refers to Example 1, and only the nickel foam is pretreated to obtain the NF material.
[0056] Comparative Example 4
[0057] The preparation method of the catalyst material provided in this comparative example refers to Example 1, with the main difference being: first, no precious metal source RuCl3·H2O is added to the raw material, and Co(OH)2 / NF nanocatalyst precursor material is obtained first; then, referring to Example 1, only RuCl3·H2O is added to the raw material, and no cobalt nitrate is added, that is, the cobalt source and the precious metal source are nucleated and grown successively, and the prepared catalyst material is marked as Ru / Co3O4-NF.
[0058] Figure 1 The SEM images of Co3O4 / NF prepared in Comparative Example 1 (a), 5-Ru-Co3O4 / NF prepared in Example 1 (b), and RuO prepared in Comparative Example 2 (c) are shown in Figure 1. x The SEM image of the Co3O4 / NF prepared in Comparative Example 1 (c) and the SEM image of the NF prepared in Comparative Example 3 (d). It can be seen from the figure that the Co3O4 / NF prepared in Comparative Example 1 has a microscopic morphology of nanosheet arrays; the 5-Ru-Co3O4 / NF prepared in Example 1 has a microscopic morphology of nanosheet arrays, and the addition of Ru does not change the morphology of Co3O4; the RuO prepared in Comparative Example 2 x / NF does not have the microscopic morphology of nanosheet arrays, but rather some loose void structures; the surface of the NF prepared in comparative example 3 is smooth and flat.
[0059] Figure 2 The XRD pattern (a) of Co3O4 / NF prepared in Comparative Example 1 and the XRD pattern (b) of 5-Ru-Co3O4 / NF prepared in Example 1 are shown. According to the XRD pattern, the crystal form of Co3O4 / NF prepared in Comparative Example 1 is No. 42-1467 in the PDF card number of the Joint Committee on Powder Diffraction Standards (JCPDS), and the Ru-Co3O4 / NF prepared in Example 1 maintains the crystal phase structure of spinel Co3O4.
[0060] Figure 3 The TEM images (a) and (b) of Co3O4 / NF prepared in comparative example 1, and the TEM images (c) and (d) of 5-Ru-Co3O4 / NF prepared in example 1. According to the selected area TEM, it can be distinguished that the main exposed crystal plane of the Co3O4 / NF nanosheet in photo (a) is the (311) crystal plane, and according to the selected area TEM, it can be distinguished that the main exposed crystal plane of the 5-Ru-Co3O4 / NF nanosheet in photo (d) is the (311) crystal plane, and Ru remains in the form of single atoms and is evenly dispersed on Co3O4.
[0061] Figure 4 The Raman graph (a) is the Raman graph of Co3O4 / NF prepared in Comparative Example 1, and the Raman graph (b) is the Raman graph of 5-Ru-Co3O4 / NF prepared in Example 1. It can be seen from the Raman graph that the Raman spectrum of Co3O4 / NF prepared in Comparative Example 1 is between 100 and 800 cm -1 There are five characteristic peaks in the range, corresponding to the F 2g 1 、E g 、F 2g 2 、F 2g 3 and A 1g Vibration model; Raman spectrum of Co3O4 / NF prepared in Example 1 is in the range of 100-800cm -1 There are five characteristic peaks in the range, corresponding to the F 2g 1 、E g 、F 2g 2 、F 2g 3 and A 1g Vibration model.
[0062] Figure 5The LSV (Linear Sweep Voltammetry) curves of 5-Ru-Co3O4 / NF prepared in Example 1 with and without glycerol added (a) and the Co3O4 / NF prepared in Comparative Example 1 and the RuO x LSV curves of Ru / Co3O4-NF prepared in Example 4, Comparative Example 4, and 5-Ru-Co3O4 / NF prepared in Example 1 with glycerol added (b). The curves in (a) are respectively with glycerol added and without glycerol added from top to bottom, and the curves in (b) are respectively with Example 1, Comparative Example 4, Comparative Example 1, and Comparative Example 2 from top to bottom. It can be seen from the figure that the current density of Co3O4 / NF prepared in Comparative Example 1 is 100 mA cm under near-neutral conditions. -2 The voltage of GOR electrocatalysis was 1.79 V vs. RHE; the current density of Ru / Co3O4-NF prepared in comparative example 4 was 100 mA cm under near-neutral conditions. -2 The electrocatalytic voltage of GOR was 1.74 V vs. RHE; the RuO prepared in Comparative Example 2 x / NF under near-neutral conditions with a current density of 10 mA cm -2 The electrocatalytic voltage of GOR was 1.78 V vs. RHE, which is far less than 100 mA cm -2 After adding glycerol, the 5-Ru-Co3O4 / NF prepared in Example 1 had a current density of 10 mA cm -2 When glycerol was not added, it shifted forward by 246 mV, indicating that the glycerol oxidation reaction was more thermodynamically favorable. -2 The GOR electrocatalytic voltage was 1.62 V vs. RHE, which was the optimal value for the implementation case.
[0063] Figure 6 The Co3O4 / NF prepared in Comparative Example 1, the 5-Ru-Co3O4 / NF prepared in Example 1, and the RuO prepared in Comparative Example 2 x 1. The Tafel slope of Co3O4 / NF prepared in Comparative Example 1 and 5-Ru-Co3O4 / NF prepared in Example 1 are shown in Figure 1, and the ECSA (electrochemically active area) curve of Co3O4 / NF prepared in Comparative Example 1 and 5-Ru-Co3O4 / NF prepared in Example 1 are shown in Figure 1. The Tafel slope of GOR electrocatalysis of Co3O4 / NF prepared in Comparative Example 1 under near-neutral conditions is 61.9 mV dec. -1The ECSA of GOR electrocatalysis under near-neutral conditions is 6.44 mF cm -1 The interface transfer impedance Rct of GOR electrocatalysis under near-neutral conditions is 5Ω; the Tafel slope of GOR electrocatalysis of 5-Ru-Co3O4 / NF prepared in Example 1 under near-neutral conditions is 33.9mVdec -1 The ECSA of GOR electrocatalysis under near-neutral conditions is 12.25 mF cm -1 The interface transfer impedance Rct of GOR electrocatalysis under near-neutral conditions is 2.5Ω; RuO prepared in Comparative Example 2 x The Tafelslope of GOR electrocatalysis of NF under near-neutral conditions is 193.1 mV dec -1 .
[0064] Figure 7 The product selectivity diagram (a) of Co3O4 / NF prepared in comparative example 1, and the C3 product selectivity and C3 product yield diagram (b). The columns in (a) are glyceric acid, glyceraldehyde, and dihydroxyacetone from top to bottom, respectively. The left y-axis in (b) corresponds to the C3 product selectivity, and the right y-axis corresponds to the C3 product yield. It can be seen from the figure that the Co3O4 / NF prepared in comparative example 1 has the highest selectivity for dihydroxyacetone product in a wide potential range, which can be maintained at ~50%. The overall C3 product selectivity in a wide potential range is >80%. The overall C3 product yield in a wide potential range shows an overall upward trend, and reaches the highest at 1.7Vvs.RHE, ~0.2mmol cm -2 h -1 .
[0065] Figure 8 The product selectivity diagram (a) and C3 product selectivity and C3 product yield diagram (b) of 5-Ru-Co3O4 / NF prepared in Example 1 are glyceric acid, glyceraldehyde, and dihydroxyacetone from top to bottom in (a), and the left y-axis in (b) corresponds to the C3 product selectivity and the right y-axis corresponds to the C3 product yield. It can be seen from the figure that the 5-Ru-Co3O4 / NF prepared in Example 1 has the highest selectivity for glyceraldehyde product in a wide potential range, which is maintained between 55-60%. The overall C3 product selectivity in a wide potential range is >90%. The overall C3 product yield in a wide potential range shows an overall upward trend and reaches the highest at 1.7Vvs.RHE, ~0.41mmol cm -2 h -1 .
[0066] Fig. 9 This is the CP (chronovoltage) curve of 5-Ru-Co3O4 / NF prepared in Example 1. As can be seen from the figure, it can-2 The device can run stably for more than 100 h at a current density of 1.5 Å, demonstrating its excellent stability.
[0067] Fig.10 The Co3O4 / NF prepared in Comparative Example 1 and the RuO prepared in Comparative Example 2 x / NF, 5-Ru-Co3O4 / NF prepared in Example 1, 7-Ru-Co3O4 / NF prepared in Example 2, 9-Ru-Co3O4 / NF prepared in Example 3, and 3-Ru-Co3O4 / NF prepared in Example 4 under the condition of adding glycerol; wherein, the curves from top to bottom are respectively Example 1, Example 2, Example 4, Comparative Example 1, Example 3, and Comparative Example 2. It can be seen from the figure that the current density of Co3O4 / NF prepared in Comparative Example 1 is 100mAcm under near-neutral conditions. -2 The GOR electrocatalytic voltage was 1.79 V vs. RHE; the current density of 5-Ru-Co3O4 / NF prepared in Example 1 was 100 mA cm under near-neutral conditions. -2 The voltage of GOR electrocatalysis is 1.62 V vs. RHE; the current density of the sample in Example 2 is 10 mA cm under near-neutral conditions. -2 The voltage of GOR electrocatalysis is 1.32 V vs. RHE; the current density of the sample in Example 3 is 10 mA cm under near-neutral conditions. -2 The voltage of GOR electrocatalysis is 1.47 V vs. RHE; the current density of the sample in Example 4 is 10 mA cm under near-neutral conditions. -2 The voltage of GOR electrocatalysis was 1.39 V vs. RHE; RuO prepared in Comparative Example 2 x / NF under near-neutral conditions with a current density of 10 mA cm -2 The GOR electrocatalytic voltage is 1.78 V vs. RHE, which is the worst performance material among all cases.
[0068] Although the content of the present invention has been described in detail through the above preferred embodiments, it should be appreciated that the above description should not be considered as a limitation of the present invention. After reading the above content, it will be apparent to those skilled in the art that various modifications and substitutions of the present invention will occur. Therefore, the protection scope of the present invention should be limited by the appended claims.
Claims
1. A low noble metal loading electrocatalyst, characterized in that: The low noble metal loading electrocatalyst comprises: a self-supporting carrier, Co3O4 nanosheets supported on the self-supporting carrier and distributed in an array, and noble metal single atoms supported on the Co3O4 nanosheets; Wherein, the noble metal single atom includes at least one of a Pt single atom, a Pd single atom and a Ru single atom.
2. The low noble metal loading electrocatalyst according to claim 1, characterized in that: The self-supporting carrier is at least one of nickel foam, copper foam, and cobalt foam, preferably nickel foam; The diameter of the Co3O4 nanosheet is 400-800nm, preferably 500-800nm, more preferably 500nm, and the thickness is 5-30nm.
3. The low noble metal loading electrocatalyst according to claim 1 or 2, characterized in that: The loading amount of Co3O4 nanosheets on the surface of the self-supporting carrier is 4-20 mg / cm 2 The mass ratio of the noble metal single atom to the Co3O4 nanosheet is 1:(50-200).
4. A method for preparing a low-noble metal-loaded electrocatalyst according to any one of claims 1 to 3, characterized in that: The preparation method comprises the following steps: (1) mixing a solution containing a cobalt source, a noble metal source and a precipitant to obtain a precursor solution; (2) placing the self-supporting carrier into the above-mentioned precursor solution to allow the cobalt source and the noble metal source to undergo nucleation growth, and washing and drying after the growth is completed to obtain a noble metal-cobalt hydroxide nanosheet array supported on the self-supporting carrier; (3) heat-treating the noble metal-cobalt hydroxide nanosheet array supported on the self-supporting carrier under a protective atmosphere to obtain the low noble metal loading electrocatalyst.
5. The preparation method according to claim 4, characterized in that: In step (1), the cobalt source is at least one of cobalt nitrate hexahydrate, cobalt sulfate heptahydrate, and cobalt chloride hexahydrate, preferably cobalt nitrate hexahydrate; The noble metal source includes at least one of a platinum source, a palladium source, and a ruthenium source; wherein: the platinum source is at least one of chloroplatinic acid hexahydrate, potassium chloroplatinate, ammonium hexachloroplatinate, and platinum acetylacetonate; the palladium source is at least one of palladium dichloride, palladium nitrate dihydrate, and palladium acetylacetonate; the ruthenium source is at least one of ruthenium trichloride hydrate, ruthenium dioxide, and ruthenium acetylacetonate, preferably ruthenium trichloride hydrate; The precipitant is at least one of urea, hexamethylenetetramine and ammonium fluoride, preferably hexamethylenetetramine.
6. The preparation method according to claim 4 or 5, characterized in that: In step (1), the mass ratio of the cobalt source to the noble metal source is 50-290:1; and the molar ratio of the cobalt source to the precipitant is 1:1-5.
7. The preparation method according to any one of claims 4 to 6, characterized in that: In step (2), 0.1 to 4 cm 2 Self-supporting carrier.
8. The preparation method according to any one of claims 4 to 7, characterized in that: In step (2), the nucleation growth process is: keeping warm at 80-150° C. for 4-16 hours.
9. The preparation method according to any one of claims 4 to 8, characterized in that: In step (3), the protective atmosphere is air, the heat treatment temperature is 300 to 550° C., preferably 350 to 550° C., and the heat treatment time is 1 to 4 hours.
10. Use of the low noble metal loading electrocatalyst according to any one of claims 1 to 3 in electrocatalytic glycerol increment oxidation under near-neutral conditions.
Citation Information
Patent Citations
Metal-doped self-supporting cobalt tetroxide nano array catalyst as well as preparation method and application thereof
CN118028890A
Low-load Ru modified Co3O4 nanosheet chlorine evolution electrocatalyst as well as preparation method and application thereof
CN118516705A
Ru-Co3O4 nano material and preparation method and electrochemical detection application thereof
CN119100460A